Shockingly Effective: Cluster Winds as Engines of Feedback in Starburst Galaxy VV 114 - Justin A. Kader; Vivian U; Jeffrey A. Rich; Marina Bianchin; Sean T. Linden; Anne M. Medling; Tanio Diaz-Santos; George C. Privon; Rosalie McGurk; Lee Armus; Loreto Barcos-Mũnoz; Gabriela Canalizo; et al. (The Astrophysical Journal, 2025)
We present high-resolution Keck Cosmic Web Imager and MUSE integral field unit spectroscopy of VV 114, a local IR-luminous merger undergoing a vigorous starburst and showing evidence of galactic-scale feedback. The high-resolution data allow for spectral deblending of the optical emission lines and reveal a broad emission line component ( σ _broad  ∼ 100–300 km s ^−1 ) with line ratios and kinematics consistent with a mixture of ionization by stars and radiative shocks. The shock fraction (percentage of ionization due to shocks) in the high-velocity gas is anticorrelated with the projected surface number density of resolved star clusters, and we find that the radial density profiles around clusters are fit well by models of adiabatically expanding cluster winds driven by massive stellar winds and supernovae (SNe). The total kinetic power estimated from the cluster wind models matches the wind + SN mechanical energy deposition rate estimated from the soft-band X-ray luminosity, indicating that at least 70% of the shock luminosity in the galaxy is driven by the star clusters. Hubble Space Telescope narrowband near-IR imaging reveals embedded shocks in the dust-buried IR nucleus of VV 114E. Most of the shocked gas is blueshifted with respect to the quiescent medium, and there is a close spatial correspondence between the shock map and the Chandra soft-band X-ray image, implying the presence of a galactic superwind. The energy budget of the superwind is in close agreement with the total kinetic power of the cluster winds, confirming the superwind is driven by the starburst.